Wildfire and drought moderate the spatial elements of tree mortality - Tucker J. Furniss; Andrew J. Larson; Van R. Kane; James A. Lutz (Ecosphere, 2020)
Abstract Background tree mortality is a complex process that requires large sample sizes and long timescales to disentangle the suite of ecological factors that collectively contribute to tree stress, decline, and eventual mortality. Tree mortality associated with acute disturbance events, in contrast, is conspicuous and frequently studied, but there remains a lack of research regarding the role of background mortality processes in mediating the severity and delayed effects of disturbance. We conducted an empirical study by measuring the rates, causes, and spatial pattern of mortality annually among 32,989 individual trees within a large forest demography plot in the Sierra Nevada. We characterized the relationships between background mortality, compound disturbances (fire and drought), and forest spatial structure, and we integrated our findings with a synthesis of the existing literature from around the world to develop a conceptual framework describing the spatio‐temporal signatures of background and disturbance‐related tree mortality. The interactive effects of fire, drought, and background mortality processes altered the rate, spatial structuring, and ecological consequences of mortality. Before fire, spatially non‐random mortality was only evident among small (1 < cm DBH ≤ 10)‐ and medium (10 < cm DBH ≤ 60)‐diameter classes; mortality rates were low (1.7% per yr), and mortality was density‐dependent among small‐diameter trees. Direct fire damage caused the greatest number of moralities (70% of stems ≥1 cm DBH), but the more enduring effects of this disturbance on the demography and spatial pattern of large‐diameter trees occurred during the post‐fire mortality regime. The combined effects of disturbance and biotic mortality agents provoked density‐dependent mortality among large‐diameter (≥60 cm DBH) trees, eliciting a distinct post‐disturbance mortality regime that did not resemble the pattern of either pre‐fire mortality or direct fire effects. The disproportionate ecological significance of the largest trees renders this mortality regime acutely consequential to the long‐term structure and function of forests.